Способ определения липоевой кислоты в биологически активных добавках методом катодной вольтамперометрии - Дорожко Е. В. Елена Владимировна; Воронова О. А. Олеся Александровна; Короткова Е. И. Елена Ивановна; Плотников Е. В. Евгений Владимирович; Вишенкова Д. А. Дарья Александровна; Дёрина К. В. Ксения Владимировна
опубл. 20.05.15